Gradivo za favno hroščev (Coleoptera) Slovenije - Brelih, Savo (Scopolia, 2006)
Based on the latest research and data from literature, index file and collections, the authors present 213 species of Longhorn Beetles (Cerambycidae) of Slovenia. A further 20 species were found in the vicinity ofits borders (up to 20 km away). The following 13 species are stated or confirmed as part of the Slovenian fauna for the very first time: Acmaeops marginatus, Cortodera femorata, Anastrangalia reyi, Vadonia unipunctata, Stromatium unicolor, Purpuricenus budensis, Xylotrechus stebbingi, X. antilope, Monochamus galloprovincialis, Pogonocherus perroudi, Opsilia uncinata, Phytoecia manicata and Oberea erythrocephala. Akimerus schaefferi, Acmaeops septentrionis, Judolia sexmaculata, Tetropium gabrieli, Glaphyra kiesenwetteri, Poecilium lividum, Parmena pubescens, Agapanthia violacea and Oberea euphorbiae are being deleted from the list of Slovenian fauna. Leptura parallela SCOP. is a n. syn. for the species Oberea linearis, Stictoleptura scutellata (FAB.) a n. syn. for Stictoleptura carbonaria, Cerambyx pulverulentus SCOP. a n. syn. for Herophila tristis, Callidium coriaceum PAYK.a n. syn. for Callidium lucidum, Stenocorus fenitus SCOP. a n. syn. for Phymatodes testaceus, Leptura bilineata a n. syn. for Saperda populnea and Leptura squallida SCOP. a n. syn. for Anogcodes rufiventris (fam. Oedemeridae).
Keywords: zoologija; zoology; entomologija; hrošči; zoogeografija; favna